THE IMPLEMENTATION OF MERDEKA CURRICULUM IN ENGLISH TEACHING LEARNING - Sari, Arum Ambar; Fatmawati, Nor Laili (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
In Indonesia, the phenomenon of curriculum change continues to experience various changes and improvements starting from the 1947 curriculum to the one that is being hotly discussed